#TITLE_ALTERNATIVE# - WIJAYA ( NIM : 12209098), ANGGI
Determination of the formation temperature in geothermal wells is a critical process to decide whether or not the next drilling program will be located in the same area. Sometime it is also needed to decide whether deepening the well is required. In extreme, inaccurate estimation of the formation temperature will lead to incorrect decisions and in turn it will make the project not feasible as the well is drilled in a low temperature area which is previously assumed as a high temperature area. To reduce the risk of misinterpreting the formation temperature, several methods to estimate the formation temperature of geothermal wells are presented. The purposes of the evaluation are to get the most accurate method and the earliest data that can be used to get a good estimate of the formation temperature. There are three methods that would be evaluated: The Horner Plot, T versus 1√𝑡 Plot (Time Root Square Method), and The Exponential Approximation. The Horner Plot Method consists of two different calculations in which each of those uses different producing time definition. The first calculation uses drilling time as the producing time while the other one uses circulation time. Analysis shows that the temperature transient travels linearly at large time for all of the methods except for the exponential approximation. The assumption for the exponential approximation is the heat flow flows through the porous media by conduction and convection mechanism, while another method does not consider the convection process which happens in early time. The data from the field have been analyzed and it shows that the exponential approximation is the most accurate method and the earlier data can be used by this method to estimate the formation temperature with a satisfactory accuracy.